Pulmonary involvement in primary biliary cirrhosis. Issue 3 (March 1981) - Rodriguez-Roisin, R; Pares, A; Bruguera, M; Coll, J; Picado, C; Agusti-Vidal, A; Burgos, F; Rodes, J
Abstract : The association of pulmonary fibrosis and primary biliary cirrhosis (PBC) remains controversial. To determine the frequency of pulmonary fibrosis in PBC, a carefully selected series of 14 PBC patients, seven patients with Sicca complex, and 14 control subjects have been studied. Seven of the 14 patients with PBC had Sjögren's syndrome, four of whom had some clinical evidence of pulmonary disease. Evaluation of ventilatory capacity, gas transfer factor, arterial blood gases, and lung mechanics were performed. Gas transfer was reduced in patients with PBC associated with Sjögen's syndrome and in patients with the Sicca complex. These results suggest that the respiratory, clinical, ad functional abnormalities found in PBC are related to the presence of an associated Sjögen's syndrome.